THE PREVALENCE AND ETIOLOGY OF POLYCYSTIC OVARIAN SYNDROME (PCOS) AS A CAUSE OF FEMALE INFERTILITY IN CENTRAL TRAVANCORE - GEORGE , K. ROY; N. A. MALINI (The Bioscan, 2014)
Recent alarming rise in the incidence of polycystic ovary syndrome (PCOS), the most common cause of female infertility is becoming a major concern among adolescent women worldwide. Altered hormonal and metabolic profiles are one of the common clinical manifestations in PCOS. The aim of the present study was to determine the prevalence and the etiology of polycystic ovary syndrome (PCOS) as a cause of female infertility in Central Travancore women, in view of their change in life style. In this cross sectional study, a consecutive series of 500 women (20-35) who were subjected to infertility treatment at specialist infertility clinics in Kottayam, Pathanamthitta and Alappuzha districts were selected. About 20 healthy volunteer females with regular menstrual cycles aged between 20 to 35 years were considered as the control. The data were collected from hospital records as well as using an investigator administered questionnaire. All data were tabulated and were subjected to statistical analysis using student’s‘t’ test, ANOVA and correlation. According to the findings of this study, PCOS is one of the most common causes of female infertility in Central Travancore women due to change in life style factors and unhealthy dietary patterns. The PCOS patients in our study also showed a wide range of hormonal and metabolic abnormalities. Insulin, FSH, LH, LH: FSH ratio, testosterone, prolactin, thyroxin (T4), progesterone, glucose and cholesterol levels were increased in PCOS. The adoption of their unhealthy dietary habits and lack of exercise are key to improving chances of these hormonal and metabolic imbalances and increasing risks of PCOS among them.